2005
DOI: 10.1097/01.alc.0000183004.28587.23
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Induced Endothelial Changes Are Associated With Oxidative Stress and Are Rapidly Reversed After Withdrawal

Abstract: Alcohol affects endothelial function with an effect that is mediated by an activated oxidative stress and is rapidly reversed after withdrawal. Dose-related endothelial responses to different alcohol intakes might translate in either vascular protection or vascular damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 46 publications
4
37
2
Order By: Relevance
“…Also, for MDA, the main marker of the lipid peroxidation processes, while several studies have found elevated levels in the serum of patients undergoing alcohol withdrawal (20,22,29), there are also reports describing clear reductions in the various markers lipid peroxidation following alcohol withdrawal (12,30).…”
Section: Discussionmentioning
confidence: 99%
“…Also, for MDA, the main marker of the lipid peroxidation processes, while several studies have found elevated levels in the serum of patients undergoing alcohol withdrawal (20,22,29), there are also reports describing clear reductions in the various markers lipid peroxidation following alcohol withdrawal (12,30).…”
Section: Discussionmentioning
confidence: 99%
“…As the scavengers of oxidants prevented those changes, oxidative stress may have a role in the alcohol-induced endothelial dysfunction. 30 It was, however, reported that the flowmediated dilation of the brachial artery and blood markers of endothelial function were similar between the usual drinking period and the alcohol restriction period in healthy men. 31 On the other hand, low concentrations of alcohol usually dilate blood vessels.…”
Section: Cardiovascular Actions Of Alcoholmentioning
confidence: 93%
“…27,28 It has been suggested that endothelin and nitric oxide are involved in alcohol-induced vasoconstriction. 29 Soardo et al 30 observed that alcohol increased the levels of endothelin-1, nitric oxide, plasminogen activator inhibitor-1 and oxidative stress both in vivo and in vitro. As the scavengers of oxidants prevented those changes, oxidative stress may have a role in the alcohol-induced endothelial dysfunction.…”
Section: Cardiovascular Actions Of Alcoholmentioning
confidence: 99%
“…Many studies have confirmed that chronic alcohol abuse is associated with important impairments in endothelial function (Di Gennaro et al, 2007;Maiorano et al, 1999;Zilkens et al, 2003). This effect is thought to be due to the increased oxidative stress produced by excessive amounts of alcohol, causing endothelial cell apoptosis (Croft et al, 1996;Soardo et al, 2005;Spyridopoulos et al, 2001;Sun & Mayhan, 2001). Large quantities of alcohol may also impair the production of nitric oxide (Persson & Gustafsson, 1992).…”
Section: Alcohol Consumption and Cvdmentioning
confidence: 98%